Assessment Of Most Common Infectious Diseases And Medicines Prescribed In The Health Posts Of Dhading District - Bajracharya, Mijala (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Infectious diseases are the communicable or transmissible diseases which are mainly caused by presence of pathogenic agents like (bacteria, virus, fungi, protozoa) in the individual host. Globally the infectious diseases contribute for 32.3% of total death and in Nepal about 70% health related problems and death are caused by infectious disease. This study was aimed to find out most common infectious diseases and medicines prescribed in its management in the health posts of Dhading district. Method: A Descriptive Cross-sectional study was conducted in three health posts of Dhading district namely Naubise health post, Bhumesthan health post and Mahadevbesi health post. 450 data were collected from record room of health posts from Shrawan 2077 to Asoj 2077. Patient related and drug related data and information were collected and analyzed. Results: The most frequent cases were Respiratory Tract Infections (22.22%), Dermatitis (11.55%) and Urinary Tract Infections (11.11%). Majority of cases were in between the age group of 21-30 years (25.11%).The average number of drugs per prescription was 2.37. The percentage of drugs prescribed by generic name and from an essential drug list of Nepal was (73.38%) and (97.46%) respectively. Out of 1067 drugs prescribed, antimicrobials (39.9%) were most commonly prescribed followed by NSAIDs (25.7%), and antihistamine (15.8%). Among antimicrobial, most commonly prescribed was amoxycillin ( 35.21%) which was followed by ciprofloxacin (16.43%) and azithromycin (14.08%). Conclusion: This study showed Respiratory Tract Infection was most common infectious disease and Amoxycillin was mostly prescribed drug.